2017
DOI: 10.1103/physrevlett.118.036401
|View full text |Cite
|
Sign up to set email alerts
|

Anderson Transition for Classical Transport in Composite Materials

Abstract: The Anderson transition in solids and optics is a wave phenomenon where disorder induces localization of the wavefunctions. We find here that the hallmarks of the Anderson transition are exhibited by classical transport at a percolation threshold -without wave interference or scattering effects. As long range order or connectedness develops, the eigenvalue statistics of a key random matrix governing transport crossover toward universal statistics of the Gaussian orthogonal ensemble, and the field eigenvectors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Ref. [52] found the phase transition to coincide with a phase transition in network connectivity due to eigenvector localization onto different connected components. Our work complements these findings, showing that a similar localization phenomenon can be onset by small communities-that is, localization does not necessarily require network fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. [52] found the phase transition to coincide with a phase transition in network connectivity due to eigenvector localization onto different connected components. Our work complements these findings, showing that a similar localization phenomenon can be onset by small communities-that is, localization does not necessarily require network fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous empirical Laplacian matrices have been observed to give rise to eigengap statistics consistent with the Wigner surmise given by (1.5) (Akemann et al [2010], Plerou et al [2002]), and we therefore believe the extended surmise given by (2.1) will also be widely applicable. Importantly, our assumption that k 1 ensures all graphs are strongly connected, which has been observed to be an important requirement for the eigengap statistics to behave similarly to that for the GOE (Murphy et al [2017]). Understanding the relation between eigengap statistics and graph topology remains an important open topic (Murphy et al [2017], Taylor et al [2017]).…”
Section: Population Covariance Matrix Ensemble: Laplacians Of K-regulmentioning
confidence: 95%
“…Importantly, our assumption that k 1 ensures all graphs are strongly connected, which has been observed to be an important requirement for the eigengap statistics to behave similarly to that for the GOE (Murphy et al [2017]). Understanding the relation between eigengap statistics and graph topology remains an important open topic (Murphy et al [2017], Taylor et al [2017]). In future work, it would be interesting to allow for graphs with more complicated structure-often called complex networks-and there is a large 1 Any Laplacian matrix C C C is positive semi-definite: v T C C Cv 0 for any vector v. Moreover, Laplacian matrices arise for many types of random processes on graphs and are related, for example, to the autocovariance matrices of random walks on graphs (Delvenne et al [2010]).…”
Section: Population Covariance Matrix Ensemble: Laplacians Of K-regulmentioning
confidence: 95%
“…The spectral measure can be numerically calculated using the discretized structure of composites [26]. It was shown that the spectral measure of random composites and the eigenvalue spacing distributions have features similar to the features of the spectra of random matrices [27] and could have a very complex structure. The idea that the convolution in the viscoelastic constitutive relation may be eliminated by introducing internal or memory variables has been efficiently used in many works in simulations of wave propagation in viscoelastic media [28][29][30][31][32][33], and in modelling and simulations of effective behaviour of linear viscoelastic composite materials [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%